Korni neba . The Roots of the Sky - Safat, Ilgar (Russia, 2003)
Duration: 00:11:00 The film is set in the Udege community, of whom only two thousand currently survive in the Far East in Russia. The filmmaker uses a collage of native paintings, footage of the surrounding nature, and foreboding sounds from the local environs to introduce community's cosmology, framed by the commentary of indigenous woman during the course of the Shaman's ritual. The film includes fragments of a 1928 documentary film Forest People by A. Litvinov which captured life in the Udege community and the Shaman's preparation for the healing ceremony.